2014
DOI: 10.1039/c4ta03691c
|View full text |Cite
|
Sign up to set email alerts
|

A simple two-step method to synthesize the well-ordered mesoporous composite Ti-FDU-12 and its application in the hydrodesulfurization of DBT and 4,6-DMDBT

Abstract: Mesoporous FDU-12 silicas with different morphologies have been synthesized under static and stirring conditions in a water bath. Furthermore, a series of mesoporous FDU-12 silicas modified by different amounts of titania have been synthesized, through a two-step method of prehydrolysis of TEOS followed by addition of titanium butoxide as a titanium precursor. Their respective NiMo supported catalysts were also prepared and characterized to elucidate the effects of titania, on the characteristics of the Mo sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 60 publications
1
68
0
Order By: Relevance
“…The peaks at 229 and 232.2 eV are attributed to Mo 3d5/2 and 3d3/2, respectively, proving the presence of Mo 4+ , in consistent with the previous report . The peaks located at 230.1 and 232.8 eV are attributed to the oxidation states of Mo 5+ and Mo 6+ , respectively, indicating the presence of partial molybdenum oxidation states . Furthermore, the peak at 226 eV could be associated to S 2 s .…”
Section: Resultsmentioning
confidence: 89%
“…The peaks at 229 and 232.2 eV are attributed to Mo 3d5/2 and 3d3/2, respectively, proving the presence of Mo 4+ , in consistent with the previous report . The peaks located at 230.1 and 232.8 eV are attributed to the oxidation states of Mo 5+ and Mo 6+ , respectively, indicating the presence of partial molybdenum oxidation states . Furthermore, the peak at 226 eV could be associated to S 2 s .…”
Section: Resultsmentioning
confidence: 89%
“…The small angle powder X‐ray diffraction (XRD) patterns of FDU‐12 and FDU‐12‐NH 2 are shown in Figure a. It exhibits three characteristic peaks, which should be assigned to the (111), (220) and (311) reflections of the face‐centred cubic structure, indicating that the mesoporous FDU‐12 and FDU‐12‐NH 2 are successfully synthesized. In addition, the intensities of each peaks are similar, which suggests that the order degree of mesoporous structure does not change after grafting .…”
Section: Resultsmentioning
confidence: 99%
“…FDU‐12 is a type of ordered mesoporous silica material with the 3‐dimensional face‐centred cubic ( Fm3 m ) structure, which has been used in catalysis, oxidation and adsorption . The window size of FDU‐12 can be tailored to around 9 nm, which is favourable for the mass transfer and diffusions of guest molecules.…”
Section: Introductionmentioning
confidence: 99%
“…As reported, the highly loaded Au/FDU‐12 catalyst exhibited an excellent antisintering property for the selective oxidation of alcohols . In addition, Zhao et al found that the mesoporous composite Ti‐FDU‐12 catalyst showed a high activity and stability for the hydrodesulfurization of DBT and 4,6‐DMDBT . Therefore, FDU‐12 may be a potential support for CO methanation.…”
Section: Introductionmentioning
confidence: 86%